Pengaruh Cara Bubur Pada Pengolahan Instant Starch Noodle Dari Pati Aren Terhadap Sifat Fisikokimia - Abdul Rahim; Haryadi Haryadi (Universitas Tadulako, 2008)
The objectives of the research were to increase the use of arenga starch and to achieve an optimal processing method of instant starch noodle made of arenga starch. In the research, the instant starch noodle was made using porridge methods. The methods of making instant starch noodle porridge including determination of starch/water ratio, duration of cooking, and optimal aging time. The starch/water ratio and duration of cooking was established based on inter-molecule binding freedom level (gelatinization and retro gradation) with a minimal score of 80% according to instant noodle requirement (SNI 01-3551-1994). While, the determination of aging time was based on physicochemical properties of instant starch noodle produced. The physicochemical properties included water content, inter-molecule binding freedom level, and cooking speed, cooking loss, tensile strength, elongation, texture and white level. The results of the research indicated that the best porridge method was done with starch/water ratio of 1:1.5 (v/v), cooking duration of 12 minute, and aging of 60 minute. Physicochemical properties of instant starch noodle porridge using such method resulting in water content of 7.62%, inter molecule binding freedom level of 82.70%, cooking speed of 2.42 minute, cooking loss of 6.15%, tensile strength of 0.018 MPa, elongation of 7.44%, texture of 10.27 N and white level of 76.30%.